2016
DOI: 10.1149/2.0151605jes
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Study on Solid Electrolyte Interphase at Li Metal Anode: Implication for Li Dendrite Growth

Abstract: The Solid electrolyte interphase (SEI), either naturally formed or artificially designed, plays a critical role in the stability and durability of Li-ion batteries (LIBs). It is even more important for high energy density electrodes such as Li metal anodes, which is subjected to large volumetric and interfacial variations due to Li deposition/stripping cycles during operation. Currently, there is a lack of understanding of the role of SEI/Li interfaces and their mechanical and electrochemical properties. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(151 citation statements)
references
References 56 publications
6
144
1
Order By: Relevance
“…For examples, SEI formation and dendrite growth of Li are regulated by the electrode-electrolyte interface; [134][135][136] stress generation and failure of the electrode materials depends on the motion and morphology of the reaction front. The correlation of the interlayer process and the degradation has motivated fundamental understanding of the interfacial processes on the one hand, and tailoring and modifying the interfaces as ways to mitigate degradation on the other.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, SEI formation and dendrite growth of Li are regulated by the electrode-electrolyte interface; [134][135][136] stress generation and failure of the electrode materials depends on the motion and morphology of the reaction front. The correlation of the interlayer process and the degradation has motivated fundamental understanding of the interfacial processes on the one hand, and tailoring and modifying the interfaces as ways to mitigate degradation on the other.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that LiF has better electron insulating property than Li 2 CO 3 is consistent with another interface model evaluating the electron potential drop at LiF/Li and Li 2 CO 3 /Li interfaces. 159 Leung and Jungjohann 160 also reported that LiF with more negative electron affinity is more effective for electron blocking than Li 2 O on Li electrode surface. Through a novel DFT/ Green's function method, Benitez et al 162,162 computed the electron transfer resistance (dV/dI) in a nano-device model consisting of an electrode and a molecule representing SEI components, such as Li 2 CO 3 , LiF, Li 2 O, or lithiated SiO 2.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 98%
“…189 DFT calculations showed that the Li 2 CO 3 /Li interface bears higher interfacial mechanical stability than LiF/Li interface. 159 However, even the maximum work of adhesion at the Li (001)/Li 2 CO 3 (001) interface is only 0.17 J m −2 , which is relatively low for typical metal/ceramics interfaces. With classical Monte Carlo (MC) and DFT-based methods, Soto and Balbuena 190 found that the oligomers attach/adhere firmly to the Li 13 Si 4 (010) surface with calculated adsorption energies in a range of 3-4 eV and if the coverage oligomer on the surface reaches approximately 1 oligomer per nm 2 , the surface-oligomer interaction will dominate the stabilization of the interface system.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
“…The Li 2 CO 3 (001)/Li(001) and LLZO(110)/Li(001) models were built following Ref. [56][57][58] . For structural relaxation and energy/density of states calculations, an energy cutoff of 520 eV and a 1´1´1 K-point Monkhorst-Pack grid were used.…”
Section: Dft Calculationsmentioning
confidence: 99%